Regal orchestra and its transformation in contemporary Malaysia / Chin Yee Wei - Chin , Yee Wei (2017)
This research examines the transformation of Regal Orchestra through the concepts of glocalization, hybridity and other factors concerning both cultural and commercial factors. Regal Orchestra started as a classical Chinese ensemble which focused on Chinese popular music, then changed its focus to provide diverse music and commercial event management services. This qualitative research is mainly based on a naturalistic inquiry approach that includes observation, interviews, virtual fieldwork and analysis on performances. Findings reveal how the group was gradually branched into diverse musical bands including fusion band, live band, jazz band, all girls crystal band, Muhibbah music band; whereas drum groups such as Tang Ren Gu, Muhibbah drum and LED water drum due to commercial influence and market demand. Due to its business nature, performances are catered according to the client’s musical taste where shidaiqu remains a favourite genre among the mid-aged and older Malaysian Chinese. Local demand of other ethnicities is answered through supplying Muhibbah drum and music performances which are by chance aligned with the 1Malaysia concept. As a summary, the study reviewed how Regal Orchestra and its changes reflect the change of tradition, political influence and as a commodity.